(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article discusses the pedagogical and psychological content of developing scientific research competencies of master’s students . It also shows that master’s students should be aware of the content of scientific approaches, concepts, theories, and the latest information in their discipline during their studies at a higher educational institution and their subsequent professional development.